What incentives encourage local communities to collect and upload mosquito sound data by using smartphones? A mixed methods study in Tanzania - Rinita Dam; Winifrida Mponzi; Dickson Msaky; Tumpe Mwandyala; Emmanuel W. Kaindoa; Marianne E. Sinka; Ivan Kiskin; Eva Herreros-Moya; Janey Messina; Syed Ghulam Sarwar Shah; Stephen Roberts; Kathy J. Willis (BMC, 2023)
Abstract Background To detect and identify mosquitoes using their characteristic high-pitched sound, we have developed a smartphone application, known as the 'HumBug sensor', that records the acoustic signature of this sound, along with the time and location. This data is then sent remotely to a server where algorithms identify the species according to their distinctive acoustic signature. Whilst this system works well, a key question that remains is what mechanisms will lead to effective uptake and use of this mosquito survey tool? We addressed this question by working with local communities in rural Tanzania and providing three alternative incentives: money only, short message service (SMS) reminders and money, and SMS reminders only. We also had a control group with no incentive. Methods A multi-site, quantitative empirical study was conducted in four villages in Tanzania from April to August 2021. Consenting participants (n = 148) were recruited and placed into one of the three intervention arms: monetary incentives only; SMS reminders with monetary incentives; and SMS reminders only. There was also a control group (no intervention). To test effectiveness of the mechanisms, the number of audio uploads to the server of the four trial groups on their specific dates were compared. Qualitative focus group discussions and feedback surveys were also conducted to explore participants' perspectives on their participation in the study and to capture their experiences of using the HumBug sensor. Results Qualitative data analysis revealed that for many participants (37 out of 81), the main motivation expressed was to learn more about the types of mosquitoes present in their houses. Results from the quantitative empirical study indicate that the participants in the 'control' group switched on their HumBug sensors more over the 14-week period (8 out of 14 weeks) when compared to those belonging to the 'SMS reminders and monetary incentives' trial group. These findings are statistically significant (p < 0.05 or p > 0.95 under a two-sided z-test), revealing that the provision of monetary incentives and sending SMS reminders did not appear to encourage greater number of audio uploads when compared to the control. Conclusions Knowledge on the presence of harmful mosquitoes was the strongest motive for local communities to collect and upload mosquito sound data via the HumBug sensor in rural Tanzania. This finding suggests that most efforts should be made to improve flow of real-time information back to the communities on types and risks associated with mosquitoes present in their houses.